Creating a Place for Learning: Dorothy Day and the Catholic Worker Movement - Marilyn McKinley Parrish (Adult Education Research Conference, 2002)
This is an examination of Dorothy Day’s approach to social activism, the development of the Catholic Worker movement, and the learning that took place within it. The intent is to contribute to a more complete history of the education of adults in twentieth century American society.